Rural Management Development: Understanding Future Scenarios for Villages in Jiroft County - Mahmoud Falsolayman; Mohammad Hajipour; Atiyeh Salari (برنامه ریزی فضایی)
AbstractRural management development is a fundamental strategy for achieving sustainable development. However, the current rural management system in Iran faces challenges, such as lack of development and inefficiency. Therefore, it is crucial to explore how rural management can address emerging issues in the future. This study focused on Jiroft County and aimed to identify the key factors and driving forces that influence rural management development. By using data analysis techniques, such as MICMAC and ScenarioWizard, along with the SOAR method, we examined the future scenarios and strategies necessary for implementation of rural management in Jiroft County. The findings revealed that 24 factors were instrumental in improving and developing rural management in the county. Among these factors, "adequate access to credits and financial resources" had the most significant impact on rural management and its development. The study highlighted that the current state of rural management in Jiroft County was largely unsustainable and it predicted that the existing conditions governing the rural management system would undergo changes in the near future. Based on the identified key factors, we generated 9 scenarios for the future development of rural management in Jiroft County. To achieve the most desirable scenario, it was essential to pursue 11 strategies and solutions. One of the proposed operational suggestions was to establish collaborative agreements with institutions and organizations both within and outside the village to effectively coordinate and manage all village affairs. Keywords: Sustainable Rural Development, Modern Rural Management, Foresight, Scenario Writing, Jiroft County.IntroductionCurrently, rural areas are confronted with heightened vulnerability and instability, presenting significant challenges to the attainment of sustainable rural development. Consequently, there have been numerous endeavors in research centers to explore scientific approaches and methods to address the impediments to rural settlement development. Rural management development emerges as a crucial and indispensable strategy in the pursuit of this objective. However, the management system in Iranian villages suffers from developmental gaps and inefficiencies within the rural sector. Given that most rural areas experience economic underdevelopment and relatively low socio-economic well-being, it becomes imperative to examine how rural management can effectively address emerging challenges in the future. Hence, this study sought to identify the key factors and drivers that influence rural management development and provided scenarios and strategies necessary for its future implementation, specifically within the geographical region of Jiroft. Materials and MethodsThis study utilized an applied research design employing a mixed-method approach. The theoretical framework was established through document analysis. The initial identification of factors impacting rural management development in Jiroft County involved a combination of document analysis and the Delphi method. The list of factors was subsequently refined using the MICMAC software for driver analysis. Scenario development was conducted employing the ScenarioWizard software and the solutions aligned with the desired scenario were identified through implementation of the SOAR method. Research FindingsIn the conducted analyses, a 24x24 matrix was utilized with repeated consideration of factors. The matrix saturation index yielded a result of 8.87%, indicating that the factors influenced each other in over 87% of cases. Out of the total 506 relationships assessed, 120 relationships (24%) exhibited high-level cross-effects (Level 3), 227 relationships (45%) demonstrated moderate-level cross-effects (Level 2), and 159 relationships (31%) displayed low-level cross-effects (Level 1).The factor with the greatest impact on the future of rural management in Jiroft County, both directly and indirectly, was "adequate access to credits and financial resources". This factor exhibited a high level of influence and susceptibility.The output generated by the ScenarioWizard software identified 9 scenarios with significant compatibility, providing potential future trajectories for rural management in Jiroft County. Among these scenarios, the first scenario obtained the highest ranking, scoring 128 points in terms of influence. Discussion of Results & ConclusionBased on the conducted investigations, it was determined that there were 24 factors that would play a significant role in enhancing and advancing rural management in the future of Jiroft County. Among these factors, "adequate access to credits and financial resources" emerged as the primary influencer on rural management and its development planning in the county. The current state of rural management in Jiroft County was characterized by a certain level of instability and it was anticipated that the prevailing conditions of the rural management system would undergo changes in the near future. Identification of these key factors enabled the generation of 9 potential scenarios for the future development of rural management in Jiroft County. Attainment of the most desirable scenario was contingent upon the implementation of 11 strategic approaches and solutions. To facilitate the development of rural management in Jiroft County, several practical suggestions are put forth. These include establishing collaborative agreements with both internal and external institutions and organizations to effectively coordinate and organize all rural affairs, drawing upon the experiences and successful management practices of accomplished village administrators in the region, and preparing comprehensive documents for rural employment and economic development that leverage local capacities. In conclusion, this study highlighted the crucial factors influencing rural management in Jiroft County and provided valuable insights into potential scenarios and strategies for its future development. By addressing these factors and implementing the recommended solutions, Jiroft County can foster sustainable rural management practices and enhance the overall well-being of its rural communities.